Wildlife strikes to civil aircraft in the United States 1990-2003 - Cleary, Edward C.; Wright, Sandra E.; Dolbeer, Richard A.; United States. Animal and Plant Health Inspection Service; United States. Federal Aviation Administration. Office of Airport Safety and Standards ([Washington, D.C.] : U.S. Department of Transportation, Federal Aviation Administration ; [Riverdale, Md.] : U.S. Department of Agriculture, Animal and Plant Health Inspection Service, Wildlife Services, 2004)
This report presents a summary analysis of data from the FAA's National Wildlife Strike Database for the 14-year period 1990 through 2003. Unless noted, all totals are for the 14-year period, and percentages are of the total known. Because of the large amount of data, Tables 2 through 17 present 14-year totals only and do not display data for individual years. In addition to the summary analysis for 1990 through 2003, a sample of significant wildlife strikes to civil aircraft in the USA during 2003 is presented at the end of the report. These strike examples demonstrate the widespread and diverse nature of the problem.
"Report of the Associate Administrator for Airports, Office of Airport Safety and Standards, Airport Safety and Certification, Washington, DC."
"Federal Aviation Administration, National Wildlife Strike Database."
Shipping list no.: 2006-0245-P.
"June 2004."
Cover title.
Includes bibliographical references (p.11-13).
Keywords: Aircraft accidents -- United States -- Statistics; Aircraft bird strikes -- United States -- Statistics